1984
DOI: 10.1111/j.1365-2133.1984.tb04699.x
|View full text |Cite
|
Sign up to set email alerts
|

Small intestinal permeability to sugars in patients with atopic eczema

Abstract: Absorption of lactulose and mannitol was measured in eleven patients with atopic eczema and lactulose/mannitol excretion ratios were calculated. Mean lactulose absorption was increased in the patients with exzema and their excretion ratios were higher than those of controls. There was no correlation between either eczema extent or severity and the excretion ratio. We conclude that small intestinal passive permeability is increased in some patients with atopic eczema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 8 publications
(8 reference statements)
3
37
0
Order By: Relevance
“…Mg deficiency results in AEDS-like symptoms in hairless rats (Neckermann et al, 2000a, b;Makiura et al, 2004). Moreover, it has also been reported that the skin barrier and also the intestinal barrier was impaired in AEDS, and consequently, intestinal permeability was enhanced, which resulted in the accumulation of sugar and fat (Ukabam et al, 1984;Kimata, 2001). Therefore, it is possible that various toxic minerals were easily absorbed and accumulated in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Mg deficiency results in AEDS-like symptoms in hairless rats (Neckermann et al, 2000a, b;Makiura et al, 2004). Moreover, it has also been reported that the skin barrier and also the intestinal barrier was impaired in AEDS, and consequently, intestinal permeability was enhanced, which resulted in the accumulation of sugar and fat (Ukabam et al, 1984;Kimata, 2001). Therefore, it is possible that various toxic minerals were easily absorbed and accumulated in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Andre et al [44] re ported an increased lactulose/rhamnose ratio in their 'food allergy' patients [44] when pro vocated by specific foodstuff while no such changes were found in children [45], PEG 600 absorption was normal and PEG 4000 increased in young patients with ecze ma, independently of any food allergy symp toms [46]. Other groups find normal PEG 400 and 1000 absorption in children with food allergy [42].…”
Section: Atopic Eczema and Food Allergymentioning
confidence: 99%
“…The re sults have, however, been conflicting. Thus, whilst some patients have had increased lac tulose and normal mannitol absorption [42], others have had normal lactulose and low rhamnose absorption [43], The cellobiose/ mannitol test is reported as abnormal in some patients with eczema despite normal jejunal histology [28]. Andre et al [44] re ported an increased lactulose/rhamnose ratio in their 'food allergy' patients [44] when pro vocated by specific foodstuff while no such changes were found in children [45], PEG 600 absorption was normal and PEG 4000 increased in young patients with ecze ma, independently of any food allergy symp toms [46].…”
Section: Atopic Eczema and Food Allergymentioning
confidence: 99%
“…It has been sug gested that changes in intestinal permeability to small water-soluble markers reflect changes in macromolec ular absorption [3,4] and are a measure of the capac ity of the gastro-intestinal tract to take up foreign an tigens.…”
mentioning
confidence: 99%